Resisting disturbing anonymity: The meaning of filiation in the philosophy of Emmanuel Lévinas - Hernández Castellón, José Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Faced with the trend of reason that reduces the human being to the general, trying to strip it of what makes it refractory to the Totality, making it manipulable, as if it were an object, its individuality must be affirmed. It must be affirmed because the characteristic of homogeneity is the instant and to remain rooted in the instant is boredom, that type of boredom that is suffering. How could we do this from the hand of the Jewish philosopher Emmanuel Lévinas? The Levinasian philosophy affirms the uniqueness of the human being, putting ethics before ontology. It is in the ethical relationship, and above all the relationship paternal-filial relationship, where Lévinas studies what happens in subjectivity when facing the other, since in it the experiences that show the way out of the imperialism of being. That is to say, in front of the son, an awakening happens to the ego insofar as it distances him from the moment, leaving the limits of time dilated.